Management Control System and Organizational Performance of Micro-finance Companies in Nepal - Singh, Prem Bahadu (The Management Review, 2026)
This research explores the impact of Management Control Systems (MCS) on the financial performance of Microfinance Institutions (MFIs) in Nepal. MFIs play a critical role in poverty reduction, financial inclusion, and growth promotion in their communities, and as these grow larger, sound management practices are essential to maintain financial performance. MCS - comprising budgeting, performance measurement and internal control offers the framework needed to support institutional practices in line with the strategic objectives. The research has adopted quantitative approach to explore the relationship between MCS and financial performance. A total of 150 financial managers and officers were asked to respond to structured questionnaires with a five-point Likert scale and ten MFIs were selected as a sample. Primary data was collected through Google Forms and secondary data was through academic literature, Nepal Rastra Bank publications and annual reports. The data was analyzed using descriptive statistics (mean and standard deviation), and inferential statistics (regression, correlation). The findings show that planning, monitoring and reporting are elements of MCS that positively affect the financial performance of the bank. Budgeting boosts productivity and profitability, while internal control systems effectively manage credit risk and improve profitability and loan recovery rates. This, in turn, augments the financial performance of the institution.